2011
DOI: 10.1007/s11033-011-1124-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken

Abstract: Calpain-3 is a skeletal muscle-specific protease and participates in the regulation of myogenesis. In this study, we quantified the expression of calpain-3 (CAPN3) mRNA in a Chinese local chicken breed (Sichuan Mountainous Black-boned chicken [MB]), to discern the tissue and ontogenic expression pattern. Meanwhile, we compared the CAPN3 mRNA expression pattern in MB chicken at 10 weeks with a commercial meat type chicken line (S01) of the same age to identify the unique expression pattern under different genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…However, in the present study, significant results were observed only for the CAPN1 gene; for the CAPN3 gene expression, only a trend was observed. For the CAPN3 gene, similar results were obtained by Zhang et al (2012), although the authors assessed CAPN3 mRNA abundance at 10 weeks of age for both slow-(the Sichuan Mountainous Black-boned chicken) and fastgrowing lines (line S01). In this study, birds characterised by high shear force (low tenderness) showed a lower level of CAPN3 gene expression than broilers with low shear force, which is consistent with the trend obtained in our study.…”
Section: Xysupporting
confidence: 56%
“…However, in the present study, significant results were observed only for the CAPN1 gene; for the CAPN3 gene expression, only a trend was observed. For the CAPN3 gene, similar results were obtained by Zhang et al (2012), although the authors assessed CAPN3 mRNA abundance at 10 weeks of age for both slow-(the Sichuan Mountainous Black-boned chicken) and fastgrowing lines (line S01). In this study, birds characterised by high shear force (low tenderness) showed a lower level of CAPN3 gene expression than broilers with low shear force, which is consistent with the trend obtained in our study.…”
Section: Xysupporting
confidence: 56%
“…Our results showed that CAPN3 was expressed in both muscle tissues, which is consistent with a report that the level of CAPN3 gene expression in the breast muscle and leg muscle was significantly higher than that in other tissues in chickens (Zhang et al, 2012). Wu et al (2015) reported high levels of CAPN3 expression in the muscle atrophic phase after denervation.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the zoological classification and suggests that CAPN3 protein is relatively evolutionarily conserved. Meanwhile, consistent with CAPN3 protein in other animals, such as cattle and chickens (Zhang et al, 2012;Pan et al, 2013;Wang et al, 2016), the Sichuan white goose CAPN3 protein has no signal peptide.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Zhang et al (2009) identified 2 SNPs (11818T>A and 12814T>G) in the CAPN3 gene in outbred strains of chicken and found associations with body weight, carcass weight, breast muscle weight, and leg muscle weight. In chickens, the CAPN3 gene was highly expressed in muscle tissues of breast and legs at ages 0, 2, 4, 6, 8, 10, and 12 months (Zhang et al, 2012).…”
Section: Snp Associationmentioning
confidence: 99%